Effectiveness of Schema-based Couples Therapy on Women’s Family Functioning - Emamipour, Hassan; Aghdasi, Alinaghi; Panahali, Amir (Psychology of Woman Journal, 2023)
Objective: The aim of the present research was to compare the effectiveness of schema-based couple therapy on the family functioning of married women.Materials and Methods: This quasi-experimental study utilized a pre-test, post-test design with a control group and a two-month follow-up period. The statistical population included all married working women in the education department of Tabriz city in 2022. The sample of this study consisted of 30 individuals who were willing to participate in the research and were selected via convenience sampling. Then, from the research sample, 30 individuals were randomly assigned to the control group and 30 individuals to the intervention group (schema-based couple therapy). Data were collected using the McMaster Family Assessment Device (FAD) (1950). The intervention of schema-based couple therapy strategies was conducted in eight 60-minute session; however, the control group did not receive any intervention. The research data were analyzed using mixed analysis of variance (with repeated measures).Findings: The results showed that the effectiveness of schema-based couple therapy on family functioning was significant (p < 0.05).Conclusion: Based on the findings of the present study, it is concluded that schema-based couple therapy is effective on family functioning in married women.